2020
DOI: 10.30597/jkmm.v2i1.8722
|View full text |Cite
|
Sign up to set email alerts
|

METODE EDUKASI & PENDAMPINGAN TERHADAP PENINGKATAN KESADARAN TERKAIT PENGGUNAAN APT PENGRAJIN PANDAI BESI

Abstract: Kesadaran akan kebisingan di sektor industri khsusnya pengrajin pandai besi umumnya belum diketahui secara luas, sehingga pekerja tidak memperhatikan risiko gangguan kesehatan berupa ketulian akibat paparan kebisingan yang melebihi standar terlebih jika mereka tidak menggunakan penutup telinga (earplug/earmuff). Studi ini merupakan penelitian kuantitatif dengan desain Quasi experiment dengan jumlah sampel 30 orang pekerja pengrajin pandai besi di Kecamatan Tellu Limpoe Kabupaten Sidrap Tahun 2018. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In addition, education provided to fishers about OSH also increased their knowledge and attitude in preventing and overcoming occupational health and safety problems so that their health status could improve (Desita, 2020). Furthermore, Wahyu (2019) reported that counseling and mentoring elevated the average knowledge score in blacksmith artisans regarding OSH, especially noise hazards in the workplace. Likewise, their attitude in the use of PPE appropriately improved.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, education provided to fishers about OSH also increased their knowledge and attitude in preventing and overcoming occupational health and safety problems so that their health status could improve (Desita, 2020). Furthermore, Wahyu (2019) reported that counseling and mentoring elevated the average knowledge score in blacksmith artisans regarding OSH, especially noise hazards in the workplace. Likewise, their attitude in the use of PPE appropriately improved.…”
Section: Resultsmentioning
confidence: 99%